Striving for Superiority Reflected in the Main Character of Angie Thomas’s the Hate U Give: A Psychological Study - Utami, Shofia Nur Rachma; Wajiran, Wajiran; Arain, Fakiha (Journal of Language and Literature Studies, 2024)
This study analyzes the main character, Starr Carter, in Angie Thomas' The Hate U Give, using Adlerian psychology to explore her drive, motivation, and development. Starr’s feelings of inferiority, stemming from her social and economic conditions, race, and traumatic experiences, are examined. The study reveals that Starr compensates for these feelings by adopting two contrasting personas: one in her predominantly white school and another in her Black neighborhood. However, as the story progresses, Starr strives for superiority by embracing her true identity and overcoming the challenges of racism, social inequality, and personal trauma. Her final goal is to unify these conflicting identities and assert her voice as a Black woman, representing her community in the fight against institutional racism. Through creative power and striving for success, Starr transforms her initial inferiority into activism, culminating in her decision to use her voice for justice, particularly following the murder of her friend, Khalil. This research contributes to understanding how Adlerian concepts apply to literary character analysis, especially in the context of racial identity and social justice.